KEEFEKTIFAN METODE PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR DAN MOTIVASI SISWA PADA PELAJARAN MATEMATIKA KELAS V SD N 02 TUMBAL PEMALANG - Izza Niâamah, Fajar Cahyadi (MALIH PEDDAS, 2013)
The problems discussed in this study is "whether there is the effectiveness of inquiry learning methods on learning outcomes and motivation of students in math class V Tumbal elementary school 02". The data in this study were obtained by using the method of documentation, tests, interviews, and questionnaires. This study is an experimental study with a quantitative approach. The design of this research study Exsperimental True Design. (Experiment truly) in the form of Posttest-Only Control Design. By using a sampling technique that is saturated sampling. Results mastery learning classical analysis by t test of the experimental group obtained t> t table (8.553> 1.676), in the control group known t <t table (1.664 <1.676). So learning by inquiry method can achieve mastery class. To determine differences in student learning outcomes using the t test, known t> t table (2.030> 2.012) then Ho is rejected, it means that the learning outcomes of the experimental group over the control group so that there are differences in learning outcomes experimental group with the control group. Calculation of the experimental group students motivation questionnaire contained 68% of students have excellent category, in the control group there were 44% of students have excellent category. So the motivation to study the experimental group was better than control group. It can be concluded that the method of inquiry learning can effectively improve learning outcomes and motivation fifth grade elementary school students 02 Tumbal.Top of Form